Dekontruksi Pemikiran Ibnu Khaldun tentang Pendidikan - Hamam Burhanuddin (Tarbiyah Departement collaboration with AMCA, 2015)
Ibn Khaldun was a gifted philosopher of history and the greatest scholars of his time, one of the leading thinkers ever born. He was a founder of the science of sociology which typically distinguishes the way it treats history as a science and provides reasons to support real events. Tradition survey of scientific conducted by Ibn Khaldun began using tradition to think scientifically and to critique the way of thinking